Karola Dejny wielki Atlas gwar polskich - Gala, Sławomir (Acta Universitatis Lodziensis. Folia Linguistica, 1995)
With the 1978 publication of his article on Main Problems of Polish Dialectology, Professor Karol Dejna a new drew attention to the need to compile the great Atlas of Polish Dialects (wielki Atlas gwar polskich – hence AGP). Being the author of many works of fundamental importance for Polish and Slavic dialectology such as Polish-Laski Linguistic Border within Polish Territory, Polish Dialects, Atlas of Polish Dialectological Innovations, co-author of regional atlases, as well as a reviewer and member of the editorial staff of Small Atlas of Polish Dialects, Karol Dejna formulates research program and its organizational framework. He elaborates the methodical basis of material collection in the form of a questionnaire-notebook of 2000 questions and an article on the Project of Material Collection for the Atlas of Polish Dialects. The project, which is currently being realized-assumes that the research will cover the whole territory of Poland, including the repolonized areas. The mentioned questionnaire notebook will, in as many as 673 points, be filled with dialect material obtained from the oldest generation of people speaking well-preserved dialect; it will also be supplemented with the old material published in the regional atlases. The collection of the material for the AGP will be combined with doing individual or collective research (by individual workers or by research centers) which would concentrate on monographic description of selected segments or points. This research, co-ordinated with the assumptions of the AGP research and covering the population and language relations, can be conducted in 19 parts of the Polish territory (selected by the Professor). The almost completed documentation has created for some segments the basis on which cartographic methods and techniques for AGP could be elaborated (Technique and Method of Cartographic Elaboration of "Atlas of Polish Dialects"; Dialect Isoglosses in the Kielce Sector of "Atlas of Polish Dialects").